New Perspectives in Statistical Modeling and Data Analysis Proceedings of the 7th Conference of the Classification and Data Analysis Group of the Italian Statistical Society, Catania, September 9 - 11, 2009 - Ingrassia, Salvatore; Rocci, Roberto; Vichi, Maurizio (Studies in Classification, Data Analysis, and Knowledge Organization,, 2011)
This volume provides recent research results in data analysis, classification and multivariate statistics and highlights perspectives for new scientific developments within these areas. Particular attention is devoted to methodological issues in clustering, statistical modeling and data mining. The volume also contains significant contributions to a wide range of applications such as finance, marketing, and social sciences. The papers in this volume were first presented at the 7th Conference of the Classification and Data Analysis Group (ClaDAG) of the Italian Statistical Society, held at the University of Catania, Italy.